2006
DOI: 10.1007/s11030-006-9033-5
|View full text |Cite
|
Sign up to set email alerts
|

Managing, profiling and analyzing a library of 2.6 million compounds gathered from 32 chemical providers

Abstract: The data for 3.8 million compounds from structural databases of 32 providers were gathered and stored in a single chemical database. Duplicates are removed using the IUPAC International Chemical Identifier. After this, 2.6 million compounds remain. Each database and the final one were studied in term of uniqueness, diversity, frameworks, 'drug-like' and 'lead-like' properties. This study also shows that there are more than 87 000 frameworks in the database. It contains 2.1 million 'drug-like' molecules among w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 38 publications
0
47
0
1
Order By: Relevance
“…False positives due to the quenching of AMC amine fluorescence were eliminated by a series of control experiments in which each compound was incubated at a concentration of 10 μmol/L with a 200 nmol/L AMC amine solution. The assay was optimized and a proprietary compound library of 65,092 chemically diverse compounds was screened for USP7 activity (23).…”
Section: Methodsmentioning
confidence: 99%
“…False positives due to the quenching of AMC amine fluorescence were eliminated by a series of control experiments in which each compound was incubated at a concentration of 10 μmol/L with a 200 nmol/L AMC amine solution. The assay was optimized and a proprietary compound library of 65,092 chemically diverse compounds was screened for USP7 activity (23).…”
Section: Methodsmentioning
confidence: 99%
“…Second, it depends on the size of the database. In general, the larger the database, the more likelihood to have more scaffolds making difficult a meaningful comparison of libraries of different size [13,25]. However, we and others have shown that large combinatorial libraries may contain a very low proportion of scaffolds as compared to smaller collections [12,18].…”
Section: Introductionmentioning
confidence: 95%
“…Em teoria, estes derivados possuem bom potencial para apresentar atividade antimalárica, somado a um bom perfil de segurança. O potencial de cada um como protótipo foi avaliado utilizando um escore (lead-like score) calculado no programa Dragon 6, baseado nos parâmetros propostos por Monge et al 54 Para os quatro compostos, foi obtido o valor ideal de 1. Ou seja, nenhum dos parâmetros moleculares utilizados para a obtenção do escore foi violado, indicando que os quatro compostos são protótipos em potencial.…”
Section: Figura 4 Resultados Dos Estudos De Validação Cruzada Lno (Aunclassified